2023
DOI: 10.3389/fonc.2022.1088931
|View full text |Cite
|
Sign up to set email alerts
|

Cuproptosis-related lncRNA signatures: Predicting prognosis and evaluating the tumor immune microenvironment in lung adenocarcinoma

Abstract: BackgroundCuproptosis, a unique kind of cell death, has implications for cancer therapy, particularly lung adenocarcinoma (LUAD). Long non-coding RNAs (lncRNAs) have been demonstrated to influence cancer cell activity by binding to a wide variety of targets, including DNA, RNA, and proteins.MethodsCuproptosis-related lncRNAs (CRlncRNAs) were utilized to build a risk model that classified patients into high-and low-risk groups. Based on the CRlncRNAs in the model, Consensus clustering analysis was used to class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…After investigating the landscape of immune and stromal cell infiltrations in both low- and high-risk groups, we found that Figure 8A illustrates how patients in the low-risk group have higher proportions of immune and stromal cell infiltrations compared to those in the high-risk group. Moreover, using the CIBERSORT algorithm ( 42 , 43 ), we calculated the immune cell proportions between the high- and low-risk groups ( Figure 8B ) and found that patients in the high-risk group significantly shared higher proportions of CD8 T cells, activated memory CD4 T cells, activated NK cells, Macrophages (M0), and Macrophages (M1). On the other hand, B cells, resting memory CD4 T cells, Monocytes, resting dendritic cells, and Activated mast cells were significantly enriched in the low-risk group.…”
Section: Resultsmentioning
confidence: 99%
“…After investigating the landscape of immune and stromal cell infiltrations in both low- and high-risk groups, we found that Figure 8A illustrates how patients in the low-risk group have higher proportions of immune and stromal cell infiltrations compared to those in the high-risk group. Moreover, using the CIBERSORT algorithm ( 42 , 43 ), we calculated the immune cell proportions between the high- and low-risk groups ( Figure 8B ) and found that patients in the high-risk group significantly shared higher proportions of CD8 T cells, activated memory CD4 T cells, activated NK cells, Macrophages (M0), and Macrophages (M1). On the other hand, B cells, resting memory CD4 T cells, Monocytes, resting dendritic cells, and Activated mast cells were significantly enriched in the low-risk group.…”
Section: Resultsmentioning
confidence: 99%
“…In this investigation, single‐sample gene set enrichment analysis (ssGSEA) 15,16 was employed to calculate the enrichment percentage of specific gene sets within each sample, facilitating the assessment of Treg enrichment values in individual specimens from The Cancer Genome Atlas‐Ovarian Cancer (TCGA‐OC) data set. The WGCNA R package served as the methodological foundation for constructing gene co‐expression networks 17 .…”
Section: Methodsmentioning
confidence: 99%
“…We screened out single cells with any gene expressed in fewer than three cells or those expressing fewer than 250 genes. The percentage of rRNA and mitochondria was then calculated with the PercentageFeatureSet function in the Seurat R package ( 22 ). Consequently, 12118 cells were totally obtained for subsequent analysis.…”
Section: Methodsmentioning
confidence: 99%
“…To further probe into the heterogeneity of ESCC, all ESCC patients were separated into different clusters according to the expression of CAF-related genes with the R package ‘ConsensusClusterPlus’ ( 22 ). Differences in survival, TIME, and immune checkpoints were evaluated among subgroups using the same methodology as previously employed.…”
Section: Methodsmentioning
confidence: 99%